1993
DOI: 10.1056/nejm199306243282503
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of Invasive Disease Due to Group B Streptococcus in Nonpregnant Adults

Abstract: Invasive group B streptococcal infection is a major problem not only in pregnant women and neonates but also in nonpregnant adults, especially those who are elderly and those who have chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
315
6
10

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(361 citation statements)
references
References 19 publications
30
315
6
10
Order By: Relevance
“…The spectrum of UTI caused by GBS includes ABU, cystitis, pyenorephritis, urethritus, and urosepsis (Bronsema et al, 1993, Farley et al, 1993, Lefevre et al, 1991, McKenna et al, 2003, Munoz et al, 1992. In many cases, GBS colonization of the urinary tract in women probably occurs by an ascending route from the vagina, where GBS can persist asymptomatically.…”
Section: Prevalence Of Gbs In the Urinary Tractmentioning
confidence: 99%
“…The spectrum of UTI caused by GBS includes ABU, cystitis, pyenorephritis, urethritus, and urosepsis (Bronsema et al, 1993, Farley et al, 1993, Lefevre et al, 1991, McKenna et al, 2003, Munoz et al, 1992. In many cases, GBS colonization of the urinary tract in women probably occurs by an ascending route from the vagina, where GBS can persist asymptomatically.…”
Section: Prevalence Of Gbs In the Urinary Tractmentioning
confidence: 99%
“…Sequencing of this but potentially life-threatening infection of deeper soft tissue, such as necrotizing fasciitis. During the late 1980s and early region revealed an open reading frame designated cpsD with significant homology to rfbP, a gene in Salmonella enterica 1990s, reports from Europe and North America suggested that the incidence of these invasive soft tissue infections has that catalyses the transfer of galactose-1-phosphate to undecaprenol phosphate, the initial step in synthesis of the Oincreased Chelsom et al 1994;Doctor et al 1995;Bisno and Stevens 1996). polysaccharide of lipopolysaccharide (Jiang et al 1991;Rubens et al 1993).…”
Section: Capsular Polysaccharidementioning
confidence: 99%
“…Urinary tract disease comprises of 5–15% of cases, including acute cystitis, pyelonephritis, asymptomatic bacteriuria, and urosepsis [4,5]. However, only a few cases of GBS intra-abdominal abscesses have been published [3,6–12].…”
Section: Introductionmentioning
confidence: 99%